Tracer hydrology in a hydrometric data-limited and complex tropical mountainous region: the case of the Central American Isthmus - Sanchez-Murillo, Ricardo (2019)
Numerous socio-economic activities are dependent on the seasonal rainfall and groundwater recharge cycle across the Central American Isthmus. Demographic growth and unregulated land use changes resulted in extensive surface in rainfall, surface water, and groundwater of Costa Rica, Nicaragua, El Salvador, and Honduras. A regional rainfall isoscape, isotopic lapse rates, spatial-temporal isotopic variations, and air mass back trajectories were combined to determine potential mean recharge elevations, moisture circulation patterns, and surface water-groundwater interactions. Intra-seasonal rainfall modes resulted in two depleted incursions (W-shaped isotopic pattern) during the wet season and two enriched pulses during the Mid-Summer Drought and the months of the strongest trade winds. Notable isotopic sub-cloud fractionation and near-surface secondary evaporation were identified as common denominators within the Dry Corridor. Groundwater and surface water isotope ratios depicted the strong orographic separation into the Caribbean and Pacific domains, mainly induced by the governing moisture transport from the Caribbean Sea, complex rainfall producing systems across the N-S mountain range, and the subsequent mixing with local evapotranspiration, and, to a lesser degree, the eastern Pacific Ocean fluxes.